A template-free synthesis of the hierarchical hydroxymethyl PEDOT tube-coral array and its application in dye-sensitized solar cells. Issue 2 (12th November 2015) - Lin, Yi-Feng; Li, Chun-Ting; Ho, Kuo-Chuan
Abstract : The hierarchical PEDOT-MeOH tube-coral array counter electrode (CE) gave a good cell efficiency of 9.13% to its dye-sensitized solar cell, suggesting its potential to replace the traditional expensive Pt CE. Abstract : A film of the hierarchical poly(hydroxymethyl 3, 4-ethylenedioxythiophene) tube-coral array (PEDOT-MeOH TCA) was successfully synthesized via a template-free electro-polymerization technique. Via a four-stage growth mechanism, the PEDOT-MeOH TCA was designed to simultaneously possess (1) enhanced conjugation on the PEDOT main chain due to the electron-donating MeOH group, (2) a decreased energy band gap due to the elevated highest occupied molecular orbital level contributed by the electron-donating MeOH group, (3) tube-like fast one-dimensional (1D) charge transfer pathways, and (4) coral-like extended electro-active sites. For the application in dye-sensitized solar cells (DSSCs), the PEDOT-MeOH TCA worked as an outstanding electro-catalytic counter electrode (CE) for iodine/triiodine (I − /I3 − ) reduction. Thus, the DSSCs with the hierarchical PEDOT-MeOH TCA as the CE reached the highest solar-to-electricity conversion efficiency ( η ) of 9.13 ± 0.06%, which was even higher than that of the DSSC with a standard Pt CE (8.94 ± 0.07%). Via various electro-chemical analyses (including cyclic voltammetry (CV), rotating disk electrode (RDE), four-point probe, Tafel polarization plot, and electrochemical impedance spectroscopy (EIS) techniques), the newly synthesized PEDOT-MeOH TCA film was found to have a lower intrinsic heterogeneous charge-transfer rate constant ( k 0 ), extremely larger effective electro-catalytic surface area ( A e ), and comparable sheet resistance ( R sh ) to those of the standard Pt film. The PEDOT-MeOH TCA can be considered as a convincing replacement of the expensive Pt due to its high electro-catalytic ability, low cost, and simple fabrication process.